THE RELATIONSHIP BETWEEN SELF-AWARENESS AND PROBLEM-SOLVING SKILLS WITH BURNOUT: COMPARISON BETWEEN JUNIOR AND SENIOR MIDWIVES IN INDONESIA - Novita, Novita; Robinson, Fredie; Sator, Patricia (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Background: Midwife burnout is a significant issue affecting healthcare quality and profession sustainability due to constant stress and shift work. Self-awareness and problem-solving skills are vital for personal and professional growth, enabling individuals to handle daily challenges independently.Objectives: This study aimed to explore the relationship between self-awareness and problem-solving skills with burnout in comparison between junior and senior midwives in Indonesia.Methods: This study employed a cross-sectional survey design at three hospitals on Indonesia's Java. The study's inclusion criteria required midwives to have a minimum of three months of experience at their present hospital. The self-awareness scale, problem-solving questionnaire, and the Maslach burnout inventory human service survey was used to measure variables. A linear regression was used to examine the relationship between self-awareness and burnout among junior and senior midwives.Results: In the junior group, respondents showed moderate self-awareness and problem-solving skills, with an average score of 3.11 (SD=1.43) and 3.56 (SD=1.93), respectively. The mean score for burnout was 3.32 (SD=1.25) , while in the senior group, self-awareness and problem-solving skills were moderate, with an average score of 3.23 (SD=1.26) and was 3.09 (SD=1.25), respectively. In junior group, education level, working unit, working experience, self-awareness, and problem-solving skills contributed significantly to burnout with R square was 43.3%. In senior group, working unit, working experience, working status, self-awareness, and problem-solving skills contributed significantly to burnout with R square was 39.8%.Conclusion: The study emphasizes the importance of monitoring and addressing burnout, as well as enhancing self-awareness and problem-solving skills among midwives. Future research should explore longitudinal variations in self-awareness, problem-solving abilities reported burnout to understand the bidirectional relationship between burnout and self-awareness.